Subtle excess in lifetime cancer risk related to CT scanning in Spanish young people. (November 2018) - Bosch de Basea, Magda; Moriña, David; Figuerola, Jordi; Barber, Ignasi; Muchart, Jordi; Lee, Choonsik; Cardis, Elisabeth
Abstract: Background: CT scan is a life-saving medical diagnostic tool, entailing higher levels of ionising radiation exposure than conventional radiography, which may result in an increase in cancer risk, particularly in children. Information about the use and potential health effects of CT scan imaging among young people in Spain is scarce. Objective: This paper aims to estimate the number of radiation-related cancer cases which can be expected due to the use of CT scanning in Spanish children and young adults in a single year (2013). Methods: The 2013 distribution of number and types of CT scans performed in young people was obtained for Catalonia and extrapolated to the whole Spain. Organ doses were estimated based on the technical characteristics of 17, 406 CT examinations extracted from radiology records. Age and sex-specific data on cancer incidence and life tables were obtained for the Spanish population. Age and sex-specific risk models developed by the Committee on Health Risks of Exposure to Low Levels of Ionizing Radiations (BEIR VII) and Berrington de Gonzalez were used, together, with the dose estimates to derive the lifetime attributable risks of cancer in Spain due to one year of CT scanning and project the number of future cancer cases to be expected. Results: In 2013, 105, 802 CT scans were estimated to have been performed in people younger than age 21. It was estimated that a total of 168.6 cancer cases (95% CrI: 30.1–421.1) will arise over life due to the ionising radiation exposure received during these CTs. Lifetime attributable risks per 100, 000 exposed patients were highest for breast and lung cancer. The largest proportion of CTs was to the head and neck and hence the highest numbers of projected cancer cases were of thyroid and oral cavity/pharynx. Conclusions: Despite the undeniable medical effectiveness of CT scans, this risk assessment suggests a small excess in cancer cases which underlines the need for justification and optimisation in paediatric scanning. Given the intrinsic uncertainties of these risk projection exercises, care should be taken when interpreting the predicted risks. Highlights: This is the 1st estimation of the CT scan use in 0-20 year old Spanish population >17, 400 CT scans were used to reliably estimate the organ-doses Chest-to-pelvis CTs conferred the highest lifetime risks The 2013 CT scanning activity would increase 0.43% the lifetime risk of cancer